Image splicing detection using HMRF superpixel segmentation - Vamsi K.; Chadha R.; Ramkumar B.; Prasad S. (My University, 2025)
Nowadays generation moves upon, digital forgeries also increasing with new trending tools for general concerns illegally. Moreover, applications are used for morphing/tampering an image to judge the world's computation. Spliced Location of any images, we pinpointed a probable approach to grab the forgery section easily and clearly. The approaches used are Super-pixels identification, Discrete Cosine Transform, Scale-invariant feature transform along with Kurtosis mapping, passive/blind forgery assumes a worthy part to search for spliced images without certain information which increases the execution of retrieval of duplicity image and consumption of time. In this proposed methodology, the controlled mechanism for 'n' iteration is calculated with the help of estimation local noise variance algorithm. Approach narrates the splicing methodology in consign way to Speculate the loop-hole detection mechanism i.e., Gives information about a traced image spliced area for verification. © 2017 IEEE.